Analysis of Content Words in the Song â€œWho Saysâ€ by Selena Gomez - Delimasari, Arrisma; Fauziah, Nisrina; Anjarsari, Dhania Puspita; Fortinasari, Paulina Besty (Institut Agama Islam Negeri Palopo, 2023)
To ensure that students can understand the meaning of the English they are learning, knowledge of content and function words are two important aspects that must be possessed. The aim is to avoid misunderstanding in the interpretation process, both in written and oral texts. Nevertheless, this research was made with the aim of knowing types of content words appeared in the lyrics of Selena Gomez's song